2015
DOI: 10.1016/j.enpol.2015.01.011
|View full text |Cite
|
Sign up to set email alerts
|

Energy conservation policies, growth and trade performance: Evidence of feedback hypothesis in Pakistan

Abstract: This study investigates the relationship between energy consumption and trade openness in Pakistan by using the annual time series data for the period of 1973-2011. Our main results show: i) the presence of long-run link between energy consumption and trade performance; ii) positive impact of gross domestic product, exports, and imports on energy consumption; iii) bidirectional causal relationship between exports and energy consumption, and also between imports and energy demand; and iv) bidirectional causalit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
41
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 94 publications
(49 citation statements)
references
References 63 publications
8
41
0
Order By: Relevance
“…Therefore, the issue of growing per capita CO 2 emissions is often used as one of the proxy indicators for measuring environmental pollutants, frequently matched with increased per capita income. Growing CO 2 emissions constitutes a major ingredient of global warming and climate change and has become a serious concern worldwide in recent years (Holtz-Eakin and Selden 1995, Kijima et al 2010, Ozturk and Acaravci 2010, Raza et al 2015. Due to the harmful effects of global warming and climate change, policy makers in developing countries have become increasingly interested in reducing the adverse effect of environmental degradation on the economy by suggesting appropriate policy tools, such as environmental taxation and increased use of renewable energy.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the issue of growing per capita CO 2 emissions is often used as one of the proxy indicators for measuring environmental pollutants, frequently matched with increased per capita income. Growing CO 2 emissions constitutes a major ingredient of global warming and climate change and has become a serious concern worldwide in recent years (Holtz-Eakin and Selden 1995, Kijima et al 2010, Ozturk and Acaravci 2010, Raza et al 2015. Due to the harmful effects of global warming and climate change, policy makers in developing countries have become increasingly interested in reducing the adverse effect of environmental degradation on the economy by suggesting appropriate policy tools, such as environmental taxation and increased use of renewable energy.…”
Section: Introductionmentioning
confidence: 99%
“…This technique also helps to identify the behavior of considered variables throughout the sample period (Raza et al 2015). Figures 3 and 4 represent the results of coefficients of FDI and workers' remittances respectively:…”
Section: Stability Of Long Run Model: a Rolling Window Analysismentioning
confidence: 99%
“…Furthermore, Cheng-Lang et al [5], Belke et al [6], Wesseh and Zoumara [7], Raza et al [8] observed a bidirectional causality between GDP and energy consumption. More complicatedly, Azam et al [9] found the existence of the long-term Granger causality moving from energy consumption to GDP for almost all ASEAN-5 countries including the Philippines, Thailand, Malaysia, Singapore, and Indonesia over 1980-2012.…”
Section: Literature Reviewmentioning
confidence: 99%